2016
DOI: 10.1002/elsc.201600136
|View full text |Cite
|
Sign up to set email alerts
|

Screening, statistical optimized production, and application of β‐mannanase from some newly isolated fungi

Abstract: Eighty‐eight fungi isolated from soil and decaying organic matter were screened for mannanolytic activity. Twenty‐eight fungi produced extracellular mannanase on locust bean gum as evidenced by zone of hydrolysis produced on mannan agar gel. Six prominent producers, including four Fusarium species namely Fusarium fusarioides NFCCI 3282, Fusarium solani NFCCI 3283, Fusarium equiseti NFCCI 3284, Fusarium moniliforme NFCCI 3287 with Cladosporium cladosporioides NFCCI 3285 and Acrophialophora levis NFCCI 3286 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Likewise, in previous studies Acrophialophora sp. was extensively studied for production of industrial enzyme [ 38 43 ] however, no report was present on antibacterial and antioxidant activity. This study reports for the first time, the potential source of anti- S .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in previous studies Acrophialophora sp. was extensively studied for production of industrial enzyme [ 38 43 ] however, no report was present on antibacterial and antioxidant activity. This study reports for the first time, the potential source of anti- S .…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic fungi mainly inhibit plant diseases through competition, lysis, and hyperparasitism [46]. Through the production of β-glucosidase, cellulose, xylanase [47,48], pectolases [49], and β-mannanase [50], the genus Acrophialophora was discovered to effectively inhibit the growth of plant pathogenic fungi. In this study, MR-57 culture filtrate inhibited F. equiseti mycelium and spore germination, resulting in mycelium malformation and rupture and a decreased spore germination rate.…”
Section: Discussionmentioning
confidence: 99%
“…27, 24, 21, and 18 nkat/ml. Soni et al (2016) screened 88 fungi for mannanase activity and found 28 fungi produced extracellular mannanase when LBG used as carbon source in liquid medium. Moretti et al (2012) isolated 27 thermophilic and thermotolerant fungal strains from self-heated habitats and screened for xylanase production.…”
Section: Xylanase and Mannanase Production In Submerged Fermentationmentioning
confidence: 99%